Factors Associated with Over-Nutrition Among Men 15-54years in Uganda: A National Survey - Arinda, Ivan Kato; Sserwanja, Quraish; Nansubuga, Sylvia; Mukunya, David; Akampereza, Phiona (Nutrition and Metabolic Insights, 2021)
Globally and in Sub-Saharan Africa (SSA), the prevalence of overweight and obesity are on the rise. Data on overweight and obesity among men are scarce.We aimed to determine the prevalence and factors associated with over-nutrition among men in Uganda.We used Uganda Demographic and Health Survey (UDHS) 2016 data of 5,408 men aged 15 to 45 years. Multistage stratified sampling was used to select study participants and data were collected using validated questionnaires. Multivariable logistic regression was used to determine factors associated with over-nutrition among 15 to 54-year-old men in Uganda.The prevalence of over nutrition was 9.1%, where that of overweight was 7.9% (95% CI 7.2-8.7 and obesity was1.2% (95% CI 0.9-1.5). Men who were aged 25 to 34 (AOR = 3.28; 95% CI: 1.92-5.59), 35-44 (AOR = 4.51; 95% CI: 2.61-7.82) and 45 to 54 (AOR = 4.28; 95% CI: 2.37-7.74) were more likely to have over-nutrition compared to those aged 15 to 24 years. Married men (AOR=2.44; 95% CI: 1.49-3.99) were 2 times more likely to have over-nutrition than men who were not married. Men in the central region (AOR = 1.78; 95% CI: 1.22-2.60) were 1.78 times more likely to have over-nutrition than men in the northern region. Men who were in the richest wealth index quintiles were 10 times more likely to have over-nutrition compared to those in the poorest wealth index quintile (AOR = 9.38: 95 % CI 5.14-17.10).The factors associated with over-nutrition among Ugandan men in our study were increasing age, marital status, increasing wealth and region of origin. This shows the need for measures to abate the regional development inequalities, need to promote physical activity among older men and need to improve on the knowledge of nutrition and dietetic practices for married couples and men of different social classes.
Keywords: Over-nutrition, prevalence, men and Uganda